Time on previous renal replacement therapy is associated with worse outcomes of COVID-19 in a regional cohort of kidney transplant and dialysis patients. Issue 10 (12th March 2021) - Villa, Luigi; Krüger, Thilo; Seikrit, Claudia; Mühlfeld, Anja S.; Kunter, Uta; Werner, Cornelius; Kleines, Michael; Schulze-Hagen, Maximilian; Dreher, Michael; Kersten, Alexander; Marx, Nikolaus; Floege, Jürgen; et al.
Abstract : Abstract: Chronic renal replacement therapy by either a kidney transplant (KTX) or hemodialysis (HD) predisposes patients to an increased risk for adverse outcomes of COVID-19. However, details on this interaction remain incomplete. To provide further characterization, we undertook a retrospective observational cohort analysis of the majority of the hemodialysis and renal transplant population affected by the first regional outbreak of severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2) in Germany. In a region of 250, 000 inhabitants we identified a total of 21 cases with SARS-CoV-2 among 100 KTX and 260 HD patients, that is, 7 KTX with COVID-19, 14 HD with COVID-19, and 3 HD with asymptomatic carrier status. As a first observation, KTX recipients exhibited trends for a higher mortality (43 vs 18%) and a higher proportion of acute respiratory distress syndrome (ARDS) (57 vs 27%) when compared to their HD counterparts. As a novel finding, development of ARDS was significantly associated with the time spent on previous renal replacement therapy (RRT), defined as the composite of dialysis time and time on the transplant (non-ARDS 4.3 vs ARDS 10.6 years, P = .016). Multivariate logistic regression analysis showed an OR of 1.7 per year of RRT. The association remained robust when analysis was confined to KTX patients (5.1 vs 13.2 years, P = .002) or when correlating the time spent on a renal transplant alone ( P = .038). Similarly, longer RRT correlated with death vs survival ( P = .0002). In conclusion our data suggest renal replacement vintage as a novel risk factor for COVID-19-associated ARDS and death. The findings should be validated by larger cohorts. Abstract : Supplemental Digital Content is available in the text